(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of positive rheumatoid factor and its association with demographic and clinical characteristics in rheumatoid arthritis patients. Study Design: Place and Duration of Study: This study was conducted at the Department of Rheumatology, Ziauddin Hospital, Karachi from June 2018 to May 2019. Materials and Methods: Patients who fulfill American College of Rheumatology (ACR) classification criteria 2010 were included in the study. The rheumatoid factor status of patients was acquired by qualitative latex agglutination test. The appearance of a detectable agglutination was considered to be a positive indicator of RF. Increased levels of ESR defined as ≥ 15 mm/hr in male and ≥ 20 mm/hr in female patients was also studied. All data were analyzed by SPSS v23.0. As the data was qualitative in nature, chi-square test was used to detect significant difference. The p-value ≤0.05 was statistically taken as significant. Results: RF was moderately higher as positive 66(75.0%). The most important result of our study was the significant correlation of RF sero-positivity with severity of symptoms specifically early morning stiffness (p=0.000) and Joint swelling (p=0.005). Conclusion: Positive Rheumatoid factor with high serum values can be correlated with early morning stiffness and joint swelling.